Oral probiotics in coronavirus disease 2019: connecting the gut–lung axis to viral pathogenesis, inflammation, secondary infection and clinical trials. (March 2021) - Baindara, P.; Chakraborty, R.; Holliday, Z.M.; Mandal, S.M.; Schrum, A.G.
Abstract: Defined as helpful live bacteria that can provide medical advantages to the host when administered in tolerable amounts, oral probiotics might be worth considering as a possible preventive or therapeutic modality to mitigate coronavirus disease 2019 (COVID-19) symptom severity. This hypothesis stems from an emerging understanding of the gut–lung axis wherein probiotic microbial species in the digestive tract can influence systemic immunity, lung immunity, and possibly viral pathogenesis and secondary infection co-morbidities. We review the principles underlying the gut–lung axis, examples of probiotic-associated antiviral activities, and current clinical trials in COVID-19 based on oral probiotics. Highlights: Probiotics are known as helpful live bacteria for medical advantages to the host when administered intolerable amounts. The study summarizes the embedded cross-road between gut and lung microbiota. Probiotics are significant solutions to improve gut health or dysbiosis created by viral infections like SARS-CoV-2. Evidence has also been given about extenuating inflammation and antiviral properties of probiotics. Probiotics can be an adjunctive treatment procedure to battle against COVID-19 and associated secondary infections.